Pengaruh Profitabilitas Dan Leverage Terhadap Audit report lag Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Rina Nurmalina (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Audit report lag occurs when a company is late in submitting financial reports. Delays in submitting these financial reports can have an impact on the level of relevance of the information contained in the financial reports, and may even indicate problems in the financial reports. Publication of financial reports is a financial report that has been audited by a public accountant, of course the auditor needs time to carry out the audit process so that this also often makes financial reports late for publication. There are several factors that can cause audit report lag. In this research, we tested the profitability and leverage variables as variables that affect audit report lag. The research was conducted namely quantitative research. The population in this study are Manufacturing Companies in the Multi-Industry Sector that are listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used purposive sampling, the total sample tested in this study were 29 companies. Company data was obtained from the official website of the Indonesia Stock Exchange. The test results conclude that simultaneously the profitability and leverage variables affect the audit report lag. And partially, profitability and leverage have a significant negatif effect on audit report lag.